KEPEMIMPINAN TRANSFORMASIONAL YANG OTENTIK DAN KECERDASAN EMOSIONAL - MM,, Siswanto, SE., (IQTISHODUNA, 2006)
The aim of this research is to analyze the influence of authentic transformational leadership directly and indirectly upon the emotional intelligence of workers Madrasah Aliyah in Jombang.  The samples of this research involved 250 participants, consist of  219 teachers and 31 employees.  Data analysis is executed by using path analysis applying the AMOS program  Output of the analysis indicate that authentic transformational leadership has a direct effect on emotional intelligence of the teachers and the employees.  Meanwhile, Authentic transformational leadership has an indirect effect mediated through value congruence on emotional intelligence’s teachers and employees.